The Complex Landscape of Polycystic Ovarian Syndrome: From Causes to Cutting-Edge Treatments - Devi S, Gokila; Kumar S, Dinesh; M, Shalini; C, Vivekanandan; Yousuf K S, Mohamed; Sharon S, Evelyn (Journal of Neonatal Surgery, 2025)
Polycystic ovarian syndrome (PCOS), or hyperandrogenic anovulation (HA), is a common endocrine condition in 4-10% of women of reproductive age globally. PCOS is diagnosed when these symptoms substantially compromise the quality of life. The etiology of the condition is multifactorial and includes genetic and environmental causes such as hormonal dysregulation, chronic low-grade inflammation, insulin resistance, and hyperandrogenism. These disrupt folliculogenesis and heighten the potential for comorbidities such as type II diabetes and endometrial cancer. New research points to dysbiosis of gut microbiota in the pathophysiology of PCOS, with disturbed microbial patterns playing a role in metabolic and hormonal dysfunction. Microbiota-directed therapy, including fecal microbiota transplantation (FMT), probiotics, synbiotics, and prebiotics, have been found to have promise in enhancing hormonal homeostasis and decreasing inflammation. This review summarizes the risk factors affecting PCOS development, prevalence, and modulation and discusses novel therapeutic approaches such as IL-22 and miRNA therapy. It highlights the importance of gut dysbiosis and examines microbiota-based treatments that may assist in the management of the heterogeneous phenotypes of PCOS, providing new directions for enhancing patient outcomes